Aging without injury in the United States requires action today. (September 2019) - Lee, Robin; Moreland, Briana
Abstract: Introduction : In 2017, unintentional injuries were the seventh leading cause of death among older adults (age ≥ 65), resulting in over 55, 000 deaths. Falls accounted for more than half of these deaths. Given that older adults are the fastest growing age group in the United States, we can anticipate that injuries will become an even greater health concern in the near future. Methods : Aging without injury is possible. There are evidence-based strategies that can reduce falls. However, older adults may not realize that falls can be prevented or they may be afraid to admit their fear of falling or difficulty with walking as these issues may signal their inability to live independently. Results : In this commentary, we will highlight what the Centers for Disease Control and Prevention is doing to prevent older adult falls. We also highlight the importance of broadening older adults' awareness about falls to successfully empower them to begin contemplating and preparing to adopt fall prevention strategies that can help them age in place. Conclusions : Older adult falls are common and can result in severe injury and death but they can be prevented. Broadening older adults' awareness about falls can empower them to take the actions necessary to reduce their fall risk. Practical applications : Increasing awareness about falls can help older adults, healthcare providers, and local and state health departments take steps to reduce fall risk.